Pharmacist-led interventions improve quality of medicine-related healthcare service at hospital discharge - Duedahl, Tina Hoff (Eur J Hosp Pharm, 2018)
OBJECTIVES: This study aims to investigate the effects on quality of the medicine-related healthcare service provided at hospital discharge after implementing a pharmacist-led patient-centred discharge service. METHODS: Medical in-patients ready for discharge and prescribed at least six medicines were eligible for inclusion in this descriptive intervention study. A ward-based clinical pharmacist provided a patient-centred discharge service which comprised medication review (including reconciliation if appropriate), medication counselling and verification of the medication discharge summary plans. Satisfaction with the pharmacist-led interventions was collected by questionnaires and follow-up telephone interviews. A quality audit on the medical information stated in the discharge summary plans was conducted. RESULTS: A total of 313 medical records were prospectively reviewed by the clinical pharmacist, and 745 medicine-related problems each leading to a clinical recommendation were identified. The total rate of acceptance by the physicians was found to be 84%. The quality audit revealed a significantly higher quality of the medication discharge summary plans sent to primary care regarding content of updated lists of medication after the pharmacist’s intervention. The involved physicians stated that contributions from the pharmacist had eased their workload and helped them to obtain a more rational prescribing practice. The interviewed patients felt secure and well-informed about their medicines. CONCLUSIONS: Contributions from clinical pharmacists can improve both the quality of and satisfaction with the medicine-related healthcare service provided at hospital discharge and secure continuity of medical care at transitions.